Control of Intracellular Calcium Signaling as a Neuroprotective Strategy - R. Scott Duncan; Daryl L. Goad; Michael A. Grillo; Simon Kaja; Andrew J. Payne; Peter Koulen (Molecules, 2010)
Both acute and chronic degenerative diseases of the nervous system reduce the viability and function of neurons through changes in intracellular calcium signaling. In particular, pathological increases in the intracellular calcium concentration promote such pathogenesis. Disease involvement of numerous regulators of intracellular calcium signaling located on the plasma membrane and intracellular organelles has been documented. Diverse groups of chemical compounds targeting ion channels, G-protein coupled receptors, pumps and enzymes have been identified as potential neuroprotectants. The present review summarizes the discovery, mechanisms and biological activity of neuroprotective molecules targeting proteins that control intracellular calcium signaling to preserve or restore structure and function of the nervous system. Disease relevance, clinical applications and new technologies for the identification of such molecules are being discussed.